2015
DOI: 10.1039/c5py00461f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating chemical ligation techniques for the synthesis of block copolypeptides, polypeptoids and block copolypept(o)ides: a comparative study

Abstract: We describe the efficient synthesis of block copolypeptides, polypeptoids as well as block copolypept(o)ides by chemical ligation techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 56 publications
(84 reference statements)
2
38
0
Order By: Relevance
“…Instead of acetylation, labeling polypeptoid stars and polypept(o)ide stars with dyes was conducted with Alexa Fluor 647 NHS ester. Further modifications at the N ‐termini with functional end groups or targeting structures are easily accessible as reported by Klinker et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of acetylation, labeling polypeptoid stars and polypept(o)ide stars with dyes was conducted with Alexa Fluor 647 NHS ester. Further modifications at the N ‐termini with functional end groups or targeting structures are easily accessible as reported by Klinker et al…”
Section: Resultsmentioning
confidence: 99%
“…Instead of acetylation, labeling polypeptoid stars and polypept(o)ide stars with dyes was conducted with Alexa Fluor 647 NHS ester. Further modifications at the N-termini with functional end groups or targeting structures are easily accessible as reported by Klinker et al [40] For further characterization of PeptoStars, the hydrodynamic diameter D h was analyzed in methanol by single-angle and multiangle DLS. Angular dependent DLS measurements were carried out in the range from 30° to 150° in 15° steps.…”
Section: Resultsmentioning
confidence: 99%
“…This underlines the living character of the polymerization known from monofunctional initiators, e.g., benzylamine, [20][21][22] n -hexylamine, [ 18 ] neopentylamine, [ 15,16,23 ] propargylamine, or 3-azido-1-propylamine. [ 12,13,24 ] A degree of polymerization of 100 and 200 has been chosen, because the hydrodynamic volume of these polymers is very similar to PEG 5000 and PEG 10 000 commonly used for block copolymers applied to micellar drug formulation currently in late clinical phases. [ 25 ] Furthermore, Huesmann as well as Birke et al recently demonstrated that PSar 200 -block -PGlu(OBn) 50 and PSar 100 -block -PGlu(OBn) 25 tend to form micelles with diameters between 40 and 60 nm desirable for drug delivery to wellvascularized solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…[ 15,23,26 ] After the controlled polymerization of the fi rst block, the end group is quantitatively quenched by acetylation by using an excess of acetic anhydride. In this step, however, also other end group functionalities can be easily introduced as reported recently by Klinker et al [ 12 ] The resulting macroinitiators can be easily purifi ed by precipitation and dialysis, freeze-dried, and applied to the next ring opening polymerization of NCAs. Therefore, the Boc protective group is cleaved under acidic conditions (TFA) yielding a primary amine functionality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation